Structural and Functional Characterization of the Enantiomers of the Antischistosomal Drug Oxamniquine. - Alexander B Taylor; Livia Pica-Mattoccia; Chiara M Polcaro; Enrica Donati; Xiaohang Cao; Annalisa Basso; Alessandra Guidi; Anastasia R Rugel; Stephen P Holloway; Timothy J C Anderson; P John Hart; Donato Cioli; et al. (Public Library of Science (PLoS), 2015)
For over two decades, a racemic mixture of oxamniquine (OXA) was administered to patients infected by Schistosoma mansoni, but whether one or both enantiomers exert antischistosomal activity was unknown. Recently, a ~30 kDa S. mansoni sulfotransferase (SmSULT) was identified as the target of OXA action.Here, we separate the OXA enantiomers using chromatographic methods and assign their optical activities as dextrorotary [(+)-OXA] or levorotary [(-)-OXA]. Crystal structures of the parasite enzyme in complex with optically pure (+)-OXA and (-)-OXA) reveal their absolute configurations as S- and R-, respectively. When tested in vitro, S-OXA demonstrated the bulk of schistosomicidal activity, while R-OXA had antischistosomal effects when present at relatively high concentrations. Crystal structures R-OXA•SmSULT and S-OXA•SmSULT complexes reveal similarities in the modes of OXA binding, but only the S-OXA enantiomer is observed in the structure of the enzyme exposed to racemic OXA.Together the data suggest the higher schistosomicidal activity of S-OXA is correlated with its ability to outcompete R-OXA binding the sulfotransferase active site. These findings have important implications for the design, syntheses, and dosing of new OXA-based antischistosomal compounds.